PEMANFAATAN FOAMING AGENT DARI MINYAK SAWIT PADA BETON RINGAN - Mukarramah Lubis; Ani Suryani; Ika Amalia Kartika; Erliza Hambali (Department of Agroindustrial Technology, Bogor Agricultural University, 2019)
Foaming agent contains surfactant that facilitates formation of foam to reduce the surface tension of liquid so that it can easily form bubbles. This time, foaming agent is used to produce lightweight concrete. Surfactant can be produced from fatty acid of palm oil named potassium palmitate and natrium laurate. The aim of this study to formulate a foaming agentfor production of lightweight concrete that could form foam that has best performances. Foaming agent for lightweight concrete was made mixturing from surfactant of potassium palmite and sodium laurate, sodium silicate and water. Design of experiment used was Completely Randomized Factorial Design with α = 5% and Duncan post hoc test with α = 5%. Analysis of variance showed consentration of surfactant and consentration of natrium silicate has significant effect in foam stability, foaming ability, foam size and surface tension.The best formulation of foaming agent was foaming agent made from 15% of surfactant, 5% of natrium silicate and 80% of water. Its performances was foam stability of 92.72%, foaming ability of 173.33%, foam size of 249.54 µm and surface tension of 27.78 dyne/cm. Keywords: foaming agent, palm oil, surfactant, sodium silicate, lightweight concrete